The Metabolic Requirements of Th2 Cell Differentiation - Stark, Julian M.; Tibbitt, Christopher A.; Coquet, Jonathan M. (Frontiers in Immunology, 2019)
Upon activation, naïve CD4+ T cells differentiate into a number of specialized T helper (Th) cell subsets. Th2 cells are central players in immunity to helminths and are implicated in mediating the inflammatory pathology associated with allergies. The differentiation of Th2 cells is dependent on transcription factors such as GATA3 and STAT-6, which prime Th2 cells for the secretion of interleukin- (IL-) 4, IL-5 and IL-13. Several lines of work now suggest that differentiating Th2 cells in the lymph node are potent IL-4 cytokine producers, but do not become competent IL-5- and IL-13-producing cells until after receiving cues from non-lymphoid tissue. It is evident that Th2 cells that enter tissues undergo considerable changes in chromatin architecture and gene expression, and that over this time, the metabolic requirements of these cells change considerably. Herein, we discuss the metabolic requirements of Th2 cells during their early and late differentiation, focusing on the impact of glucose and lipid metabolism, mTOR activation, the nuclear receptor PPAR-gamma and several metabolites.